2016
DOI: 10.1016/j.jconrel.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Rotating magnetic field induced oscillation of magnetic particles for in vivo mechanical destruction of malignant glioma

Abstract: Magnetic particles that can be precisely controlled under a magnetic field and transduce energy from the applied field open the way for innovative cancer treatment. Although these particles represent an area of active development for drug delivery and magnetic hyperthermia, the in vivo anti-tumor effect under a low-frequency magnetic field using magnetic particles has not yet been demonstrated. To-date, induced cancer cell death via the oscillation of nanoparticles under a low frequency magnetic field has only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 33 publications
1
109
0
11
Order By: Relevance
“…Compared to the micro-scale magnetic materials, nanomaterials are easily internalized by cells 39, and the intracellular cell membrane destruction has been proven to be more efficient than the disruption from the cell surface 23. Furthermore, the magnetic field in this study is safe and its frequency substantially lower than the risk level in adults 40.…”
Section: Introductionmentioning
confidence: 84%
“…Compared to the micro-scale magnetic materials, nanomaterials are easily internalized by cells 39, and the intracellular cell membrane destruction has been proven to be more efficient than the disruption from the cell surface 23. Furthermore, the magnetic field in this study is safe and its frequency substantially lower than the risk level in adults 40.…”
Section: Introductionmentioning
confidence: 84%
“…Although MNPs represent an area of active development for MHT, the in vivo anti-tumor effect under a low-frequency magnetic field using MNPs has not yet been demonstrated. A study by Cheng et al (94) demonstrated the successful use of spin-vortex, disk-shaped permalloy magnetic particles in a low-frequency, rotating magnetic field for the in vitro and in vivo destruction of glioma cells. In addition, the hysteresis loss is also important for MHT, as increasing the hysteresis loss is improving the heating efficiency (94).…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…A study by Cheng et al (94) demonstrated the successful use of spin-vortex, disk-shaped permalloy magnetic particles in a low-frequency, rotating magnetic field for the in vitro and in vivo destruction of glioma cells. In addition, the hysteresis loss is also important for MHT, as increasing the hysteresis loss is improving the heating efficiency (94). A study by Sasayama et al (95) examined the hysteresis loss of magnetically fractionated MNPs for hyperthermia application.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…They also speculated that the mechanical oscillation of microdiscs attached to the cancercell membrane may be transformed into an ionic electrical signal, which triggers the programmed cell-death pathway. Cheng et al demonstrated that a low frequency (20 Hz), rotating magnetic field could induce the rotating of spinvortex, disk-shaped permalloy magnetic particles, creating enough mechanical force that can destruct cell membrane of glioma cells [43]. A swing magnetic field with low frequency and low heat-production was designed by Chen et al in order to evaluate the torque effect of magnetotactic bacteria on S. aureus (Figures 2(a) and 2(b)) [44].…”
Section: Under Constant or Low Frequency Magnetic Fieldmentioning
confidence: 99%